Nursing Care for Mrs H Who Has Chronic Renal Failure with Hypervolemia Nursing Problems in The Bougenville Room General hospital Dr. H. Koesnadi Bondowoso - Wardani, Hamidah Retno; Azzahro, Indah Novita; Agustin, Leni (Universitas Bondowoso, 2023)
Background: Chronic Kidney Disease (CKD) is damage to the kidneys both in structure and/or function that lasts for 3 months or more. The purpose of this writing is to carry out Nursing Care for Clients Experiencing Chronic Kidney Disease (CKD) with Hypervolemia Nursing Problems. Method: This study used a case study research design with one of the clients who experienced Chronic Kidney Disease (CKD) with Hypervolemia nursing problems in the Bougenville Room General hospital Dr. H. Koesnadi Bondowoso, starting from May 15, 2023 – May 17 2023, data collection was in the form of interviews, observations, physical examinations, documentation studies and questionnaires. Results: The results of this study were obtained from the study, namely hypervolemia in accordance with the theory, diagnosis according to the theoretical review. In nursing interventions according to the circumstances experienced by the client, while the implementation refers to predetermined interventions and evaluation refers to the outcome criteria that have been set in accordance with the theory. Clients are expected to be able to keep physically fit by exercising, keeping blood sugar levels normal, keeping blood pressure normal. Conclusion: Patients with chronic kidney disease often experience hypervolemia which is accompanied by an increase in laboratory results in the form of creatinine and ureum levels. then management is needed in improving patient hydration in the form of input and output as well as improving renal physiological anatomy through haemodialysis intervention in patients.